The influence of boreal biomass burning emissions on the distribution of tropospheric ozone over North America and the North Atlantic during 2010 - Parrington, M.; Palmer, P. I.; Henze, D. K.; Tarasick, D. W.; Hyer, E. J.; Owen, R. C.; Helmig, D.; Clerbaux, C.; Bowman, K. W.; Deeter, M. N.; Barratt, E. M.; Coheur, P. F.; et al. (Digital Commons @ Michigan Tech, 2012)
We have analysed the sensitivity of the tropospheric ozone distribution over North America and the North Atlantic to boreal biomass burning emissions during the summer of 2010 using the GEOS-Chem 3-D global tropospheric chemical transport model and observations from in situ and satellite instruments. We show that the model ozone distribution is consistent with observations from the Pico Mountain Observatory in the Azores, ozonesondes across Canada, and the Tropospheric Emission Spectrometer (TES) and Infrared Atmospheric Sounding Instrument (IASI) satellite instruments. Mean biases between the model and observed ozone mixing ratio in the free troposphere were less than 10 ppbv. We used the adjoint of GEOS-Chem to show the model ozone distribution in the free troposphere over Maritime Canada is largely sensitive to NOx emissions from biomass burning sources in Central Canada, lightning sources in the central US, and anthropogenic sources in the eastern US and south-eastern Canada. We also used the adjoint of GEOS-Chem to evaluate the Fire Locating And Monitoring of Burning Emissions (FLAMBE) inventory through assimilation of CO observations from the Measurements Of Pollution In The Troposphere (MOPITT) satellite instrument. The CO inversion showed that, on average, the FLAMBE emissions needed to be reduced to 89% of their original values, with scaling factors ranging from 12% to 102%, to fit the MOPITT observations in the boreal regions. Applying the CO scaling factors to all species emitted from boreal biomass burning sources led to a decrease of the model tropospheric distributions of CO, PAN, and NOx by as much as -20 ppbv, -50 pptv, and -20 pptv respectively. The modification of the biomass burning emission estimates reduced the model ozone distribution by approximately -3 ppbv (-8%) and on average improved the agreement of the model ozone distribution compared to the observations throughout the free troposphere, reducing the mean model bias from 5.5 to 4.0 ppbv for the Pico Mountain Observatory, 3.0 to 0.9 ...